Hegemonía y cultura política en el Partido Comunista de Chile: la transformación del militante tradicional, 1924 - 1933 - Urtubia, Ximena (Ariadna Ediciones, 2016)
History of the first decades of Communist Party of Chile, its political culture, and the changes produced by Bolshevisation